TANTANGAN DAN PELUANG DALAM MEWUJUDKAN PENDIDIKAN BERKUALITAS BAGI MASYARAKAT DI ERA REVOLUSI INDUSTRI 4.0 MELALUI SCHOOL BRANDING : STUDI KASUS SEKOLAH SWASTA DI BALI - Kusumawati, Niluh Ari (JAPAM (Jurnal Pendidikan Agama), 2024)
In the context of education in the era of the industrial revolution 4.0, VUCA (Volatility, Uncertainty, Complexity, Ambiguity) is a very serious challenge in realizing quality education. Education in the era of the industrial revolution 4.0 tends to change very quickly both in the context of technology use, learning methods and social trends. In this case educators must be able to have high adaptability to various changes that occur in the world of education. The emergence of artificial intelligence such as artificial intelligence (AI), Internet of Things (IoT), big data, chatgpt and so on has an impact on learning methods, curriculum, and the need for new skills that must be owned by educators and students. Focusing on the problems currently faced by several schools in Bali, especially private schools, is a very significant decrease in the number of students. Competition with public schools can be a challenge for private schools. Public schools generally have lower fees or are even free, which can entice parents to enroll their children in public schools. This can result in reduced student numbers and revenue for private schools. Improvement of the private school management system in Bali needs to be done so that private schools can continue to exist. To overcome these problems school branding can be a solution in realizing quality education. School branding by utilizing digital technology as a solution, so that private schools can exist and compete again in the world of education.